IMPLEMENTATION OF LAND USE FOR PALM OIL PLANTATIONS BY THE INDRAGIRI HILIR COMMUNITY IN THE AREA FORESTS THROUGH SUSTAINABILITY MECHANISMS PLANTING ACCORDING TO THE LAW JOB CREATION - Siregar, Samsul Bahri; Kadaryanto, Bagio; Yalid (International Peneliti Ekonomi, Sosial dan Teknologi, 2026)
The resolution of community plantation issues within forest areas needs to prioritize legal certainty and protection for farmers, among others through area arrangement schemes, recognition of community rights, and non-litigation settlement policies in accordance with applicable laws and regulations. This research aims to analyze the implementation of the use of oil palm plantation land in forest areas through the planting encroachment mechanism based on the Job Creation Law, as well as to analyze the obstacles and efforts to address the implementation of such use of land through the same mechanism. The method employed is sociological legal research. Based on the research findings, the implementation of the use of oil palm plantation land in forest areas through the planting encroachment mechanism under the Job Creation Law constitutes a corrective policy aimed at organizing factual land control conditions that occurred prior to the enactment of the law. This policy marks a shift in the law enforcement approach from a repressive administrative model toward structuring that emphasizes legal certainty, community protection, and the sustainability of forest area management. In practice, the planting encroachment mechanism provides a settlement space for business actors and cultivating communities who were previously in a condition of legal uncertainty. The obstacles in implementing the use of oil palm plantation land in forest areas through the planting encroachment mechanism under the Job Creation Law include uncertainty regarding the status and boundaries of forest areas, regulatory disharmony and technical policy inconsistencies, limited institutional capacity, low levels of public dissemination, and the suboptimal involvement of indigenous law communities. These conditions result in the planting encroachment mechanism not yet fully providing legal certainty and substantive justice as envisaged by the Job Creation Law.